Activation of Alpha Chymotrypsin by Three Phase Partitioning Is Accompanied by Aggregation - Rather, Gulam Mohmad; Mukherjee, Joyeeta; Halling, Peter James; Gupta, Munishwar Nath (PLOS ONE, 2012)
Precipitation of alpha chymotrypsin in the simultaneous presence of ammonium sulphate and t-butanol (three phase partitioning) resulted in preparations which showed self aggregation of the enzyme molecules. Precipitation with increasing amounts of ammonium sulphate led to increasing size of aggregates. While light scattering estimated the hydrodynamic diameter of these aggregates in the range of 242–1124 nm; Nanoparticle tracking analysis (NTA) gave the value as 130–462 nm. Scanning electron microscopy and gel filtration on Sephadex G-200 showed extensive aggregation in these preparations. Transmission electron microscopy showed that the aggregates had irregular shapes. All the aggregates had about 3× higher catalytic activity than the native enzyme. These aggregates did not differ in λmax of fluorescence emission which was around 340 nm. However, all the aggregates showed higher fluorescence emission intensity. Far-UV and near-UV circular dichroism also showed no significant structural changes as compared to the native molecule. Interestingly, HPLC gel filtration (on a hydroxylated silica column) gave 14 nm as the diameter for all preparations. Light scattering of preparations in the presence of 10% ethylene glycol also dissociated the aggregates to monomers of 14 nm. Both these results indicated that hydrophobic interactions were the driving force behind this aggregation. These results indicate: (1) Even without any major structural change, three phase partitioning led to protein molecules becoming highly prone to aggregation. (2) Different methods gave widely different estimates of sizes of aggregates. It was however possible to reconcile the data obtained with various approaches. (3) The nature of the gel filtration column is crucial and use of this technique for refolding and studying aggregation needs a rethink.